Assessment of iodine concentration in dietary salt at household level in Morocco - Ahmed Zahidi; Meriem Zahidi; Jamal Taoufik (BMC, 2016)
Abstract Background Following WHO recommendations, Morocco adopted in 1995 the universal salt iodization (USI) as a strategy to prevent and control iodine deficiency disorders. In 2009, the standard salt iodine concentration was adjusted to 15-40 mg/kg. The success of USI for the control of iodine deficiency disorders requires an evaluation of iodine concentration in salt prior to assessing the iodine nutritional status of a population. Methods In our study we refer to the anterior studies that were made in Morocco in 1993 and 1998. 178 salt samples from households were tested for iodine using spot-testing kits. The iodometric titration method was used to analyze accurately the concentration of iodine in the 178 household salt samples. An empiric polling method was adopted, using a non-probability sampling method; across the different twelve regions in the country. Results The median and interquartile range iodine concentration in salt was 2.9 mg/kg (IQR: 2.4-3.7). The results show that only 25 % of households use iodized salt. The recommended iodine concentration in salt of 15-40 mg/kg was met only in 4.5 % of salt samples. The bulk salt is used by 8 % of households. All samples of this bulk salt were found in rural areas. According to nonparametric appropriate tests used, there is no significant difference in iodine concentrations between regions, between urban and rural areas and between packaged and bulk salt. Conclusions Two decades since introducing legislation on Universal Salt Iodization, our survey shows that generalization of iodized salt is far from being reached. In 2015, only a quarter of Moroccan households use the iodized salt and only 4.5 % of salt is in conformity with regulations. The use of bulk salt by households in rural areas constitutes a major obstacle to the success of USI. The National Iodine Deficiency Disorders Control Program can only be achieved if an internal follow-up and a control of external quality of program is put in place.